4r-2=3r+6

Simple and best practice solution for 4r-2=3r+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4r-2=3r+6 equation:


Simplifying
4r + -2 = 3r + 6

Reorder the terms:
-2 + 4r = 3r + 6

Reorder the terms:
-2 + 4r = 6 + 3r

Solving
-2 + 4r = 6 + 3r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-3r' to each side of the equation.
-2 + 4r + -3r = 6 + 3r + -3r

Combine like terms: 4r + -3r = 1r
-2 + 1r = 6 + 3r + -3r

Combine like terms: 3r + -3r = 0
-2 + 1r = 6 + 0
-2 + 1r = 6

Add '2' to each side of the equation.
-2 + 2 + 1r = 6 + 2

Combine like terms: -2 + 2 = 0
0 + 1r = 6 + 2
1r = 6 + 2

Combine like terms: 6 + 2 = 8
1r = 8

Divide each side by '1'.
r = 8

Simplifying
r = 8

See similar equations:

| 2(3x+4)-2x=x+17 | | 3f=999 | | 3-4[2-(5y-8)]= | | 4x-3x-6=21 | | -7-3x=8+2 | | 4x+x-3x+7=2x+x | | 8(x+.5)=2x+4 | | -5(2x-9)=2(x-8) | | 4x^2-10=-6x | | 2c+4-3c=-9+c+15 | | 7C+1=50 | | x-4.5=3 | | 10.6p+15=205.8 | | 10=50x | | 8s-12=52 | | -x-3x+20=x | | 3xyz-y+4x-y= | | 45p=168 | | 2f-81=11 | | 27=x+14 | | -36-9x=-12x+3 | | (5x-2)(7x+8)= | | 2(1/2x+1)=-3(2x-1)+4(2x+1) | | -8x+-3x= | | 2x=3x-22 | | 3r-7=17r | | 400p+20=680 | | 2x+x+2x=126 | | 32.8=8n | | 9s=-20 | | (-3+2i)-(4-4i)= | | 7-2p=12p |

Equations solver categories